2023
DOI: 10.1186/s12967-023-04405-y
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-melanocyte stimulating hormone (α-MSH): biology, clinical relevance and implication in melanoma

Luigi Dall’Olmo,
Nicole Papa,
Nicoletta Concetta Surdo
et al.

Abstract: Alpha-melanocyte stimulating hormone (α-MSH) and its receptor, melanocortin 1 receptor (MC1R), have been proposed as potential target for anti-cancer strategies in melanoma research, due to their tissue specific expression and involvement in melanocyte homeostasis. However, their role in prevention and treatment of melanoma is still debated and controversial. Although a large body of evidence supports α-MSH in preventing melanoma development, some preclinical findings suggest that the α-MSH downstream signalli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 96 publications
0
3
0
Order By: Relevance
“…Microphthalmia-transcription factor serves as a key transcription factor responsible for the regulation of melanogenesis by activating the transcription of TYR, TRP-1, and TRP-2. Consequently, the downregulation of MITF and these enzymes leads to a decrease in melanin production [ 62 ]. This investigation aimed to evaluate the ethanolic extract of G. atroviridis fruits on the mRNA expression levels of MITF, TYR, TRP-1, and TRP-2 in α-MSH-stimulated B16F10 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Microphthalmia-transcription factor serves as a key transcription factor responsible for the regulation of melanogenesis by activating the transcription of TYR, TRP-1, and TRP-2. Consequently, the downregulation of MITF and these enzymes leads to a decrease in melanin production [ 62 ]. This investigation aimed to evaluate the ethanolic extract of G. atroviridis fruits on the mRNA expression levels of MITF, TYR, TRP-1, and TRP-2 in α-MSH-stimulated B16F10 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Our study demonstrated that CSK effectively reduced α-MSH-induced melanogenesis in melanocytes without causing cytotoxicity, exhibiting efficacy comparable to arbutin—a recognized skin-lightening agent. Ultraviolet-stimulated ROS in skin cells stimulate α-MSH through MC1R, inducing melanin synthesis [ 61 ]. Our results showed the increased melanin content of melanocytes following α-MSH treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, mainly eumelanin is synthesised in the presence of cysteine and sufficient MC1R activity [18]. α-MSH, a paracrine factor secreted by keratinocytes as a result of UVR exposure, binds to MC1R as an agonist and activates adenylyl cyclase [19], ultimately generating a cyclic AMP (cAMP) signalling cascade for the transcription of the MITF and its downstream transcriptional targets, which are enzymes involved in eumelanin synthesis, namely tyrosinase, tyrosinaserelated protein 1, and tyrosinase-related protein 2 (Tyr, TRP1, TRP2) [20]. Based on the review from [8].…”
Section: Intrinsic Regulation Of Pigmentation In Melanocytesmentioning
confidence: 99%